2019
DOI: 10.3390/sports7010029
|View full text |Cite
|
Sign up to set email alerts
|

Drop Jump Asymmetry is Associated with Reduced Sprint and Change-of-Direction Speed Performance in Adult Female Soccer Players

Abstract: Studies that examine the effects of inter-limb asymmetry on measures of physical performance are scarce, especially in adult female populations. The aim of the present study was to establish the relationship between inter-limb asymmetry and speed and change-of-direction speed (CODS) in adult female soccer players. Sixteen adult players performed a preseason test battery consisting of unilateral countermovement jump (CMJ), unilateral drop jump (DJ), 10 m, 30 m, and 505 CODS tests. Inter-limb asymmetry was calcu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

15
129
5
5

Year Published

2020
2020
2025
2025

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 88 publications
(154 citation statements)
references
References 41 publications
15
129
5
5
Order By: Relevance
“…No significant relationships were present between asymmetry scores, highlighting the independent nature of the selected tests in elite youth male soccer players ( Table 2). This finding is supported by previous studies (Loturco et al, 2018;Bishop et al, 2019c), which stated a lack of relationships between different asymmetry scores in both female and male elite senior soccer players. Furthermore, in a recent study, Bishop et al (2018a) observed that when comparing asymmetry scores across multiple tests levels of agreement were typically poor.…”
Section: Discussionsupporting
confidence: 90%
“…No significant relationships were present between asymmetry scores, highlighting the independent nature of the selected tests in elite youth male soccer players ( Table 2). This finding is supported by previous studies (Loturco et al, 2018;Bishop et al, 2019c), which stated a lack of relationships between different asymmetry scores in both female and male elite senior soccer players. Furthermore, in a recent study, Bishop et al (2018a) observed that when comparing asymmetry scores across multiple tests levels of agreement were typically poor.…”
Section: Discussionsupporting
confidence: 90%
“…This observation could be explained by local strength asymmetries show higher magnitudes. Negative influence of asymmetry in vertical drop jump height and COD performance (180 • turn test) (r = 0.66, p < 0.01 and 0.52, p < 0.05; depending on the side of the turn) was found by Bishop et al [21]. Also, using horizontal jumps to assess asymmetries, Madruga-Parera et al [38] found much lower correlations (r = 0.32 and 0.31, p <0.05) between asymmetry in horizontal jumping length (SLLJ) and COD performance (V-cut and 180 • turn test).…”
Section: Discussionmentioning
confidence: 80%
“…By contrast, few studies have found a significant correlation between global asymmetry in jumping tests and COD performance. Studying female soccer players, Bishop et al [21] found a significant positive correlation between inter-limb asymmetry in single-leg depth jump height and performance in 505 COD test on left (r = 0.66, p < 0.01) and right (r = 0.52, p < 0.05) side. Another study that reported a relationship between asymmetry and performance was of Maloney et al [22], that explained 63% (p < 0.001) of variance of COD performance with leg stiffness and height asymmetry during vertical depth jump.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, Bishop et al [7] showed that jump height asymmetry (12.5%) from the SLCMJ was associated with slower 5m (r = 0.49; p < 0.05), 10m (r = 0.52; p < 0.05) and 20m (r = 0.59; p < 0.01) sprint performance in youth female soccer players. In addition, Bishop et al [18] showed that drop jump asymmetries were associated with slower acceleration, speed and COD performance in adult female soccer players. Specifically, jump height asymmetry was correlated with 30m (r = 0.58; p < 0.05) and 505 (r = 0.52-0.66; p < 0.05), and reactive strength index asymmetry was correlated with 10m (r = 0.52; p < 0.05) and 505 on both limbs (r = 0.54-0.55; p < 0.05).…”
Section: Introductionmentioning
confidence: 99%